2013
DOI: 10.1007/s11524-013-9805-z
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Experiences of Violence and Relation to Violence Perpetration beyond Young Adulthood among an Urban Sample of Black and African American Males

Abstract: The purpose of this study is to determine if experiences of physical violence during early and late adolescence (12-21 years) places urban Black males at increased risk for interpersonal violence perpetration beyond young adulthood (30 years and older). Participants of this cross-sectional study were Black and African American men (N0455) between the ages of 30 and 65 years, recruited from four urban clinical sites in the Northeast. Multivariate logistic regression models were used to analyze the relation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…As with our findings, Vervoort, Scholte, and Overbeek (2010) found that ethnic minorities were more likely to bully others compared to the dominant ethnic group; however, once accounting for ethnic composition of a classroom (i.e., higher proportions of minority ethnic groups in a classroom), this effect disappeared. Discrimination is actively perpetrated toward Māori and other nondominant ethnic groups in New Zealand secondary schools (Crengle, Robinson, Ameratunga, Clark, & Raphael, 2012), and discrimination is strongly associated with violence perpetration (Caldwell, Kohn-Wood, Schmeelk-Cone, Chavous, & Zimmerman, 2004;Reed et al, 2014). We found few school-level organizational factors (such as school size, single-sex or coeducational schools, and private or public funding) that were associated with bullying behaviors among students once student composition was taken into account.…”
Section: Discussionmentioning
confidence: 79%
“…As with our findings, Vervoort, Scholte, and Overbeek (2010) found that ethnic minorities were more likely to bully others compared to the dominant ethnic group; however, once accounting for ethnic composition of a classroom (i.e., higher proportions of minority ethnic groups in a classroom), this effect disappeared. Discrimination is actively perpetrated toward Māori and other nondominant ethnic groups in New Zealand secondary schools (Crengle, Robinson, Ameratunga, Clark, & Raphael, 2012), and discrimination is strongly associated with violence perpetration (Caldwell, Kohn-Wood, Schmeelk-Cone, Chavous, & Zimmerman, 2004;Reed et al, 2014). We found few school-level organizational factors (such as school size, single-sex or coeducational schools, and private or public funding) that were associated with bullying behaviors among students once student composition was taken into account.…”
Section: Discussionmentioning
confidence: 79%
“…These questions were used to ask respondents about use of force with partners in the past year: [22] 1) Pushing, grabbing or shoving; 2) Slapping, kicking, biting or hitting; 3) Threatening his/her partner with a weapon like a knife or gun; 4) Cutting or bruising partner; 5) Forcing partner to have sex; and 6) Injuring partner enough so that he/she needed medical attention. Each IPV perpetration variable was categorized into a binary construct, Once/2 to 3 times/Once a month/More than once a month versus Never, as has been used in previous studies [5861], before being used as a latent variable in structural equation modeling (SEM) [46]. The use of latent variables allows for the reduction of a large number of observed variables into an overall theme.…”
Section: Methodsmentioning
confidence: 99%
“…Six questions from the Conflict Tactic Scales (Straus and Gelles, 2009), which have been validated in a population-based sample (Moffitt and Caspi, 1997), were used to ask respondents about use of force with partners in the past year (Roberts et al, 2011). Many previous studies have categorized IPV in the past year into a dichotomous variable (Moffitt and Caspi, 1997; Finneran and Stephenson, 2014; Ramirez et al, 2012; Reed et al, 2013). All intimate partner aggression variables were categorized into a binary construct: Once/2 to 3 times/Once a month/More than once a month vs. Never.…”
Section: Methodsmentioning
confidence: 99%